Djamaluddin Wak Ketok: Work From Struggle to Independence in Padang City (1945-1959) - Fatmi Fauzani Duski; Ernawati Ernawati (Science and Environmental Journal for Postgraduate, 2022)
This article discusses the work of Djamaluddin Wak Ketok during the struggle for independence and after independence. Then it will also discuss the role of Djamaluddin Wak Ketok in improving the economy of the community as well as his struggle career during the independence period and after independence. This article uses historical and library methods consisting of several stages, namely heuristics, source criticism, interpretation, and historiography. The source used is the primary source in the form of observations, documentation, and interviews conducted with family or the public who know Wak Keto. This article shows that Djamaluddin Wak Ketok started his career when in 1945 he returned to Padang and became a member of the Indonesian Youth Information Center (BPPI) Padang City. Then became vice chairman at the Independence Struggle Council in Padang City, became the Head of AKR/TKR/TRI in Padang, Division IX Leader of sector IV/A commander based in AsamPulauAnduring front area of Padang Area and Padang Luar Kota, until his position as military district officer (PDM) in Pasaman Lubuk Sikaping became the career peak of Djamaluddin Wak Ketok. Wak Ketok role is that he is a respected figure of the community, Indonesian freedom fighters, his exaltation, and his religion. Djamaluddin Wak Ketok work in building public roads, now named Djamaluddin Wak Ketok Street from Simpang Pisang Pauh to Simpang Pasar Ambacang Kuranji Sub-district. Another great service is to build with matual tali bandar, irrigation for irrigation of rice fields from Gunung Nago Kuranji Sub-district, through Nanggalo, to Belanti Village, North Padang.